Public research, open science and innovation: creating the path for sustainable resource-led industrialisation in Malaysia - Alavi, Rokiah; Abdul Ghani Azmi, Ida Madieha (International Association of Computer Science and Information Technology, 2013)
This paper intends to demonstrate the importance of innovation in primary resources by the government research institutes (GRIs) and the practice of open science in creating the path for resource-led and knowledge-intensive industrialisation in Malaysia. The core argument here is that a successful resource -led industrialisation lies on the technological advancement in the primary resources developed by GRIs . The focus of this study is on rubber industry and research undertaken by the Malaysian Rubber Board (MRB). Research methods used were interviews and secondary data search. It is found that R&D undertaken by rubber research centres and their open science practice have sustained Malaysia’s quest to be the leading producer and exporter of natural rubber and rubber based products